Mechanisms of acute ankle syndesmosis ligament injuries in professional male rugby union players: a systematic visual video analysis - Delahunt, E.; Farrell, G.; Boylan, A.; Kerin, F.; Tierney, P.; Hogan, H.; Boreham, C. (British Journal of Sports Medicine, 2021)
Background: The mechanisms of acute ankle syndesmosis ligament injuries in professional rugby union are not well understood.